Aligning Electronic and Protonic Energy Levels of Proton‐Coupled Electron Transfer in Water Oxidation on Aqueous TiO21. Issue 45 (23rd July 2014) - Cheng, Jun; Liu, Xiandong; Kattirtzi, John A.; VandeVondele, Joost; Sprik, Michiel
Abstract The high overpotential in water oxidation on anodes is a limiting factor for the large‐scale application of photoelectrochemical cells. To overcome this limitation, it is essential to understand the four proton‐coupled electron transfer (PCET) steps in the reaction mechanism and their implications to the overpotential. Herein, a simple scheme to compute the energies of the PCET steps in water oxidation on the aqueous TiO2 surface using a hybrid density functional is described. An energy level diagram for fully decoupled electron‐ and proton‐transfer reactions in which both electronic and protonic levels are placed on the same potential scale is also described. The level diagram helps to visualize the electronic and protonic components of the overpotential, and points out what are needed to improve. For TiO2, it is found that its catalytic activity is due to aligning the protonic energy levels in the PCET steps, while improving the activity requires also aligning the electronic levels.